2021
DOI: 10.1007/s43545-021-00233-3
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of social justice in mathematics classrooms

Abstract: This study explored the challenges faced by mathematics teachers in promoting social justice in teaching and learning in mathematics in high schools in Nepal. An interpretive qualitative research method was employed for collecting, analyzing, and interpreting data in an iterative process. An in-depth interview method was implemented to collect data from three mathematics teachers on challenges of social justice in mathematics classrooms at three public secondary schools in Kathmandu. A multi-layered thematic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 66 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…Some of the respondents reported having had no mathematics teachers in their earlier schooling at certain points in time, having part-time mathematics teachers who taught varied topics all at different times without integrating the flow of ideas in the lessons, absentee teachers (some due to intermittent ill health), large classes, issues of assessment and reporting to students. While Panthi et al (2021) reported absenteeism of students in their study, it was teachers who were reported absent in this study. These were matters of concern as far as mathematics for social justice principles were to be addressed.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Some of the respondents reported having had no mathematics teachers in their earlier schooling at certain points in time, having part-time mathematics teachers who taught varied topics all at different times without integrating the flow of ideas in the lessons, absentee teachers (some due to intermittent ill health), large classes, issues of assessment and reporting to students. While Panthi et al (2021) reported absenteeism of students in their study, it was teachers who were reported absent in this study. These were matters of concern as far as mathematics for social justice principles were to be addressed.…”
Section: Discussionmentioning
confidence: 57%
“…The exploration of mathematics as a tool for social justice in education remains a vibrant area of research. While Panthi et al's (2021) studies focused on challenges that preclude students from experiencing mathematics for social justice in Kathmandu's mathematics classrooms, Gutstein's (2003) students experience positive collaboration among students and between parents. This enabled effective technology integration with a deeper understanding of society and inequality through mathematics.…”
Section: Empirical Studiesmentioning
confidence: 99%
“…Studies focuses on the mathematics teaching and related problem during online teaching such as teaching-learning issues in mathematics (Panthi et al, 2021), challenges faced by the learners (Dhakal, 2022), factors associated with the challenges in teaching mathematics online (Adhikari et al, 2022), problem of mathematics teacher in teaching mathematical content online , teachers' Perceptions on effect of information and communication technologies , teachers' perceptions toward student support in using information and communication technology in mathematics learning . indicate that Algebra, Statistics, Vectors, Geometry, and Analysis are problematic areas for teachers teaching mathematics online and other mentioned above literature focused on the effect of using digital resources teachers' professional development and learning performance in the context of Nepal.…”
Section: Open Accessmentioning
confidence: 99%